INTERPRETATION OF GRAVITY AND MAGNETIC DATA TO PREDICT THE POTENTIAL STRUCTURES OF MINERALS IN THE AREAS OF SOUTH - SOUTHEAST VIETNAM WATERS - Dung, Tran Tuan; Dung, Bui Viet; Hung, Nguyen The (Vietnam Journal of Marine Science and Technology, 2016)
The East Vietnam Sea is a marginal sea with complicated geological structures. The volcanic activities are quite strong after the sea-floor spreading in Cenozoic Era. There are the types of structure here favorable to the formation of solid minerals (manganese-iron aggregation). However, it is difficult to define their ranges and spatial locations. This paper presents the methods of reduction to the magnetic equator in low latitudes to bring out a better correlation between magnetic anomalies and their sources; High-frequency filtering is to separate gravity and magnetic anomalies as well as information about the solid minerals in the upper part of the Earth’s crust; 3D total gradient is to define the spatial location of high density and magnetic bodies. The potential structures of solid mineral are predicted by multi-dimensional correlation analysis between high frequency gravity and magnetic anomalies with weighted 3D total gradient.